Join in at Johannesburg 2002 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The World Summit on Sustainable Development (also known as Rio + 10) will be a summit gathering from 2 - 11 September 2002 in Johannesburg, South Africa, of governments, citizens, UN agencies, financial bodies and other major actors to assess global...